2017
DOI: 10.3802/jgo.2017.28.e39
|View full text |Cite
|
Sign up to set email alerts
|

Germline and somatic mutations in homologous recombination genes among Chinese ovarian cancer patients detected using next-generation sequencing

Abstract: ObjectiveTo define genetic profiling of homologous recombination (HR) deficiency in Chinese ovarian cancer patients.Methodswe have applied next-generation sequencing to detect deleterious mutations through all exons in 31 core HR genes. Paired whole blood and frozen tumor samples from 50 Chinese women diagnosed with epithelial ovarian carcinomas were tested to identify both germline and somatic variants.ResultsDeleterious germline HR-mutations were identified in 36% of the ovarian cancer patients. Another 5 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 36 publications
(59 reference statements)
7
31
1
Order By: Relevance
“…The quality of the data that can be obtained from FFPE tissues as opposed to fresh tissues needs clarification. The fact that the distribution of somatic mutations was consistent with other Chinese studies (36,48) and with a Polish study using FFPE tissues from HGSC patients (52) could guarantee the quality of our sample preparation. It was suggested that an adjusted targeted capture-based enrichment protocol was superior to commonly applied multiplex PCRbased protocols for reliable BRCA1/2 variant detection, including CNV detection, using FFPE tumor samples (53).…”
Section: Discussionsupporting
confidence: 87%
“…The quality of the data that can be obtained from FFPE tissues as opposed to fresh tissues needs clarification. The fact that the distribution of somatic mutations was consistent with other Chinese studies (36,48) and with a Polish study using FFPE tissues from HGSC patients (52) could guarantee the quality of our sample preparation. It was suggested that an adjusted targeted capture-based enrichment protocol was superior to commonly applied multiplex PCRbased protocols for reliable BRCA1/2 variant detection, including CNV detection, using FFPE tumor samples (53).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have presented the involvement of radiation repair protein 52 (RAD52) in the cell cycle control as well as DNA repair, and depletion of RAD52 could cause synthetic lethality in BRCA1 mutant breast cancer cells (Hromas et al, 2017). Additionally, several groups have conferred RAD52 as novel risk loci in ovarian cancer patients (Stafford et al, 2017; Zhao et al, 2017), underlining its significant effects on controlling cancer cell activities. In conclusion, all elements in these five triplets contribute cohesively to the development of ovarian cancer through regulating cell cycle and growth.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates of the contribution of germline BRCA mutations to EOC vary widely, from 5% to 20% [20], and patients having somatic mutations without germline mutations in BRCA are less frequent, accounting for 2%-8% [21][22][23][24]. Germline and somatic BRCA mutation frequencies in EOC patients, according to the published literature, are listed in Table 5 [4, [23][24][25][26][27]. As for HGSC, the lowest frequency of germline and somatic BRCA mutations (21.8%) is recorded in TCGA 2011 data, with the highest (20/47, 42.6%) in the present study.…”
Section: Discussionmentioning
confidence: 99%